A comprehensive review of magnetorheological fluid assisted finishing processes. Issue 3 (4th May 2022) - Rajput, Atul Singh; Das, Manas; Kapil, Sajan
Abstract: In today's manufacturing sector, it is required to manufacture products that have an exceptionally low tolerance. The desired high precision (or low tolerance) can be obtained through various finishing processes, which consist of bonded (honing, grinding, lapping, etc.) or unbonded (abrasive flow finishing) forms of the tool. An unbonded form of tool is more reliable and beneficial because it helps to achieve a highly polished surface without affecting the material topography of the product. The literature survey shows that an effective unbonded form of finishing tool can be produced through the assistance of Magnetorheological (MR) Fluid, as it has in-situ control on its rheological properties. The MR fluid is mainly composed of abrasives and ferromagnetic powder mixed in a viscoplastic base medium. The unbonded multipoint cutting tool is generated during the finishing operations, which produces a mirror-like polished surface. Several MR fluid-assisted finishing processes have been developed in the last few decades. This article explores the evolution of MR fluid-assisted finishing processes, along with their development, applications, influencing process parameters, the composition of MR fluids, and governing analytical models. The key capabilities and limitations of different MR fluid-assisted finishing processes are also discussed, and a comparison is made to provide an overview at a glance.